Optimization of leaching of copper to enhance the recovery of gold from liberated metallic layers of WPCBs - Dhanunjaya Rao M.; Shahin C.; Jha R. (My University, 2025)
Waste printed circuit board (WPCB) of any electronic gadget is a source of valuable metals such as copper, nickel, gold, silver etc. Alternatively, WPCB also contains various toxic elements which cause environmental pollution effects while exposed to the incineration and landfilling. Recycling of WPCBs is requisite to reduce the ecological impact and to recover the valuables. In this article, a hydrometallurgical route for the extraction of copper, i.e. pre-treatment and leaching of copper from WPCBs is studied by the optimization of various parameters. Initially, WPCBs are downsized to 1x1 cm2and then the metallic fraction is separated by the delamination of WPCB layers by treating them with an organic solvent dimethylacetamide (DMA) at 160°C for 10h. Liberated metallic fraction is used for the leaching of copper without any selective dissolution of gold. Influence of various parameters such as type of leaching reagent, the concentration of the solution, temperature and time are optimized. Results have shown that nitric acid is a suitable reagent for copper leaching than other solvents at room temperature (30 °C). Optimum results revealed that 3M nitric acid with 50g/L pulp density at 500rpm stirring speed in 2h had shown effective leaching (99.9%) of copper with no gold dissolved in the leach solution. © 2021 Elsevier Ltd. All rights reserved.